Holistic Comprehensive Approach to Conquer Allergy - Allergic Rhinitis with Homoeopathic Modality (Homoeopathy for All, 2026)
Allergic rhinitis is a common  disorder that is usually a long standing condition that often goes  undetected in the primary-care  setting. The classical manifestation  of the disorder are nasal congestion,  nasal itch, rhinorrhea and sneezing.  A thorough history, physical  examination and allergen skin  testing are important for establishing  the diagnosis of allergic rhinitis.  Rhinitis is classified into one of the  following categories according to  etiology: IgE-mediated (allergic),  autonomic, infectious and idiopathic  (unknown). This article provides  an overview of the aetiology,  diagnosis, and appropriate general  & homoeopathic management of  allergic rhinitis.
Keywords: classical manifestation; physical examination; allergy-causing; pollen or dust